(untitled) (Academic Journal of Internal Affairs, 2018)
Several home experts dealt already with problems of management security at mass events (e.g. Dsupin Ottó, Hajas Barnabás). In an earlier paper of mine I also payed attention – from another aspect – to management security of major events, but experiences show that this topic is not exhausted yet, there are opportunities for advances in home practice yet. In the present paper, partially under use of own experiences, I partly try to disclose problems and deficiencies of security management and potential error sources by examination of the effective normative regulations and also make proposals how to avoid them.